IL-10 family cytokines in chronic rhinosinusitis with nasal polyps: From experiments to the clinic - Xuan, Lijia; Zhang, Nan; Wang, Xiangdong; Zhang, Luo; Bachert, Claus (Frontiers in Immunology, 2022)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is considered a nasal sinus inflammatory disease that can be dominated by immune cells and cytokines. IL-10 family cytokines exert essential functions in immune responses during infection and inflammation. Recently, the understanding of the roles of the IL-10 family in CRSwNP is being reconsidered. IL-10 family members are now considered complex cytokines that are capable of affecting epithelial function and involved in allergies and infections. Furthermore, the IL-10 family responds to glucocorticoid treatment, and there have been clinical trials of therapies manipulating these cytokines to remedy airway inflammatory diseases. Here, we summarize the recent progress in the understanding of IL-10 family cytokines in CRSwNP and suggest more specific strategies to exploit these cytokines for the effective treatment of CRSwNP.